Poirot. Series 3 [videorecording (DVD)] - Suchet, David; Fraser, Hugh; Jackson, Philip, 1948-; Christie, Agatha, 1890-1976 (ITV Studios Home Entertainment ; Distributed by Acorn Media, 2012)
Agatha Christie's brilliant Belgian detective is on the case in the third series of the hit PBS mystery. Fan favorite David Suchet stars as the dapper sleuth who solves the thorniest of cases with his formidable intellect. Set in glittering 1930s Europe, these remastered adaptations capture every splendid detail of the Art Deco era.